What do Cochrane systematic reviews say about congenital vascular anomalies and hemangiomas? A narrative review - Guedes Neto, Henrique Jorge; Kuramoto, Danielle Akemi Bergara; Correia, Rebeca Mangabeira; Santos, Brena Costa; Borges, Amanda da Cunha; Pereda, Mariana Raffo; Aidar, Ana Laura e Silva; Pereira Júnior, Francisco Amadeu; Amaral, Fabio Cabral de Freitas; Vasconcelos, Vladimir Tonello de; Lustre, Wellington Gianoti; Amorim, Jorge Eduardo de; et al. (São Paulo Medical Journal, 2022)
BACKGROUND: Congenital vascular anomalies and hemangiomas (CVAH) such as infantile hemangiomas, port-wine stains and brain arteriovenous malformations (AVMs) impair patients’ lives and may require treatment if complications occur. However, a great variety of treatments for those conditions exist and the best interventions remain under discussion. OBJECTIVE: To summarize Cochrane systematic review (SR) evidence on treatments for CVAH. DESIGN AND SETTING: Review of SRs conducted in the Division of Vascular and Endovascular Surgery of Universidade Federal de São Paulo, Brazil. METHODS: A broad search was conducted on March 9, 2021, in the Cochrane Database of Systematic Reviews to retrieve any Cochrane SRs that assessed treatments for CVAH. The key characteristics and results of all SRs included were summarized and discussed. RESULTS: A total of three SRs fulfilled the inclusion criteria and were presented as a qualitative synthesis. One SR reported a significant clinical reduction of skin redness by at least 20%, with more pain, among 103 participants with port-wine stains. One SR reported that propranolol improved the likelihood of clearance 13 to 16-fold among 312 children with hemangiomas. One SR reported that the relative risk of death or dependence was 2.53 times greater in the intervention arm than with conservative management, among 218 participants with brain AVMs. CONCLUSION: Cochrane reviews suggest that treatment of port-wine stains with pulsed-dye laser improves redness; propranolol remains the best option for infantile hemangiomas; and conservative management seems to be superior to surgical intervention for treating brain AVMs.